A Parametric Study for Drilling High Quality Holes on Glass Fiber Composites - Yilmaz, Cagatay; Kesriklioglu, Sinan (My University, 2022)
The objective of this study is to investigate the effect of cutting parameters on the qual- ity of holes drilled in a glass fiber reinforced thermoset polymer with the delamination factor defined as the ratio of intended hole diameter to the diameter of the maximum area which contains both hole and delaminated area. For this purpose, Taguchi's L9 or- thogonal array was used to design the experiments and optimize the drilling parameters. 5 mm twist drill bits were used to drill the holes at various feeds and spindle speeds. The maximum diameters on the inlet and outlet sides of the holes drilled into the composite plates were then measured with an optical microscope to analyze the influence of the drilling parameters on the machining damage. The smallest delaminated area on the front and back sides of the composite plate was achieved with the lowest feed (0.05 mm/rev) for the drilling parameters used in this study. Even though the spindle speed was increased from 318 rpm to 2930 rpm at a constant feed of 0.05 mm/rev, it reduces the maximum diameter on the front and back sides by 9 μm and 266 μm, respectively. The obtained results showed that the material removal rates in the drilling of the glass fiber reinforced thermoset polymers can be increased significantly by setting the optimized process pa- rameters without adversely affecting the hole quality.
Keywords: Malzeme Bilimleri; Tekstil; İmalat Mühendisliği; Malzeme Bilimleri, Tekstil